Innovation and capability building of MSME “Las Yayang” and its local economic contribution - Mardiana R; Yossinomita Yossinomita; Eni Rohaini; Erick Morales; Erna Stelawati (University of Merdeka Malang, 2025)
One well-known home-based business that produces peyek and chips and plays a strategic role in enhancing both household welfare and regional economic is Las Yayang. Nevertheless, Las Yayang also faces several challenges, including limited production capacity, difficulties in maintaining accurate financial records, and a reliance on conventional marketing methods. The solutions provided include the provision of an automatic slicing machine and a continuous band sealer machine to enhance productivity, assistance in digital financial recording using the MYOB Premier, as well as training in digital marketing through Facebook and e-commerce platforms, particularly Toko Shopee. The program outcomes showed an increase in production capacity, more organized and accurate financial records, and the expansion of marketing reach. Participants’ knowledge also increased by an average of 30 percent–40 percent, with the highest improvement seen in operating automatic machines. This program has had a tangible impact on home-based entrepreneurs, like improved production efficiency, management professionalism, and contributions to local economic growth through increased partner revenues. The program will continue with further assistance related to optimizing digital financial management using MYOB, advancing digital marketing strategies, and fostering product innovation. Therefore, enables the home-based entrepreneurs to sustain business growth and contribute to the development of a circular economy.